Saudi government revenues and expenditures : a financial crisis in the making - Aldukheil, Abdulaziz M.; SpringerLink (Online service). (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Will history repeat itself, leaving Saudi Arabia to face another financial crisis due to drastic overspending and/or a dramatic drop in oil revenue? If the situation remains on its current trajectory, by 2030 government debt due to rising expenditures over revenues will be too overwhelming for the government to cope with.
Keywords: Science